The Use of the Short-Cut Graphic Method of Multiple Correlation - Malenbaum, Wilfred; Black, John D. (Quarterly Journal of Economics, 1937)
Methodological Background, 69. — The Method, 72. — The Indexes of Correlation, 76. — Omitted Variables, 77. — Inadequate Data, 87. — Independent Variables Intercorrelated, 88. — Joint Curvilinear Correlation, 92. — Joint Correlation Using Flexible Methods, 96. — Conclusions, 105.